WILDLIFE TOURISM: A SYNTHESIS OF PAST, PRESENT, AND FUTURE RESEARCH AGENDA - Kanta, Kota Neela Mani; Kaurav, Rahul Pratap Singh; Allam, Uday Sankar; Srivalli, P (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Wildlife tourism (WT) is an emerging sector of tourism, majorly meant to view and/or encounter wildlife in the wild, captive, and semi-captive settings. Because of the new emerging economies, there is an increased demand for wildlife destinations in both, developing and developed nations. However, a comprehensive study is lacking in WT. In this context, the present study seeks to bring together and discuss the key findings on WT from the present literature and propose new approaches to research using co-citation, co-authorship, and co-occurrence analyses. Further, the study also considers research on WT conducted so far like attitudes, bird-watching, conservation, economics, hunting, mammals, management, marine monitoring, negative impacts, positive impacts, captive wildlife, and guidelines. A data set is created that includes authors, article titles, citations, countries, co-authorship, institutions, publication years and sources, keywords, and abstracts by collecting the bibliographies from Scopus and Web of Science (WoS) indexed journals with keywords search “Wild Life, Jungle and Tourism.” The study collected 1,519 and used 1,259 published articles from 1990 to 2020, and analyzed employing VOS viewer software, which has enabled us to understand the relationship and structure of the literature.